A new species of crab-eating rat of the genus Ichthyomys, from Ecuador (Rodentia, Cricetidae, Sigmodontinae) - Fernández de Córdova, Javier (2019)
Based on two adult specimens collected in the Río León (Azuay, Ecuador), we describe a new highland species of a small crab-eating rat of the genus Ichthyomys Thomas (Rodentia, Cricetidae, Ichthyomyini). It is distinguishable from Ichthyomys hydrobates (Winge, 1891), the species phenetically closest to it, by its smaller size, bicolored tail (unicolored in I. hydrobates), broad and heavily fringed hindfoot (narrower and moderately fringed in I. hydrobates), and several craniodental traits (e.g. rostrum short broad; nasals anteriorly truncated; interorbital region narrow; supraorbital margins smoothly rounded; supraorbital foramina small, zygomatic plate very narrow; incisors opisthodont; length of M3 half that of M2). The new species occurs in the western Andes in southern Ecuador and is allopatric with Ichthyomys stolzmanni Thomas, 1893, which also has a bicolored tail but is larger. The new species brings the number of Ecuadorean Ichthyomys to four, Ecuador thus becoming the country with the greatest diversity of Ichthyomyini (four genera and eight species).